Long-Term Follow-Up of Single-Fiber Multiple Low-Intensity Energy Laser Ablation Technique of Benign Thyroid Nodules - Squarcia, Mattia; Mora, Mireia; Aranda, Gloria; Carrero, Enrique; Martínez, Daniel; Jerez, Ramona; Valero, Ricard; Berenguer, Joan; Halperin, Irene; Hanzu, Felicia A. (Frontiers in Oncology, 2021)
Aim The short-term and long-term efficacy of different thermal percutaneous ablation techniques remains a topical issue. Our group implemented percutaneous laser ablation (LA), a moving-shot technique to increase efficiency and reduce costs and variability of LA by applying multiple lower-intensity energy illuminations (MLIEI) covering the nodular volume (V) through changes in position of a single laser fiber within the thyroid nodule. The aim of the present study was to evaluate the efficacy of the single-fiber LA-MLIEI during a 5-year follow-up and to identify possible predictors of the final outcome. Methods Prospective study: Thirty outpatients (23 women and seven men) with benign symptomatic thyroid nodules were assigned to single-fiber LA-MLIEI, between 2012 and 2015. A single LA session was performed under real-time ultrasound (US) guidance using a 1,064-nm continuous-wave laser at 3 W. A 400-µm optical fiber was inserted through a 21-gauge needle, and 3–10 illuminations were performed per nodule, administering between 400 and 850 J/illumination. The total administered energy was calculated on the initial V of the nodule and the estimated ablation area. US evaluation was performed after LA-MLIEI at 1 week and 1, 3, 6, and 12 months and after that annually up to 5 years. Clinical symptoms, laboratory thyroid function during follow-up, and acute and chronic complications of treatment were registered. Results On follow-up, 67% (n: 20) were responders to single-fiber LA-MLIEI, while 33% (n: 10) were non-responders. The responder group initiated V reduction (ΔV) at 1 month, with remission of symptoms, and presented a 50% ΔV at 3 months of treatment; the maximum response was achieved at 24 months and remained stable until the end of the study. The non-responder group presented a ΔV of less than 50% at 12 months; though a tendency to >50% ΔV was observed at 24–36 months, there was subsequent regrowth, and 40% of this group required surgery. ΔV was positively correlated with the total administered energy/V (J/V) and inversely with nodule V. No severe adverse effects were observed. Thyroid function remained normal in all patients. Remission of symptoms occurred rapidly after 1 month. Conclusions LA with multiple fractional discharges employing a single fiber in a unique session is a safe and inexpensive technique that allows rapid reduction of thyroid nodules, with a stable response up to 5 years, similarly to what has been reported with the conventional LA. Total nodule volume appears as a predictive factor of the reduction.